(untitled) (Journal of Economics and Sustainability, 2023)
On 1st May 2022, the Malaysian government raised the minimum wage (MW) to RM1,500, with a 25% increase. Even though there seem to be some signs of economic recovery, the Malaysian economy has yet to crawl out of a downturn. MW has been one of the most debated and controversial topics in economic literature due to mixed results on employment. While it may be too early for any empirical study on the impact of this recent hike, we are not completely clueless about what to expect. This paper aims to offer valuable insights into the potential implications of the new minimum wage policy (MWP) through a narrative literature review approach. Although no conclusive prediction can be made, the literature on developing countries with high MW increases seems to suggest that higher disemployment, reduced foreign worker dependency, formal sector (FS) migration to the informal sector (IS), and higher non-compliance are likely to be expected. This paper contributes to the understanding of MW in developing countries. Based on the channel of adjustment (CoA) model, alternate suggestions are offered to small and medium enterprises (SMEs) to better cope with the financial stress caused by MWP.